2011
DOI: 10.1017/s1461145710001513
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of treatment outcome in major depression

Abstract: There is a need to identify clinically useful biomarkers in major depressive disorder (MDD). In this context the functional connectivity of the orbitofrontal cortex (OFC) to other areas of the affect regulation circuit is of interest. The aim of this study was to identify neural changes during antidepressant treatment and correlates associated with the treatment outcome. In an exploratory analysis it was investigated whether functional connectivity measures moderated a response to mirtazapine and venlafaxine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 73 publications
3
64
0
Order By: Relevance
“…With regard to studies of treatment effects, reductions in functional connectivity observed here encompass the region lesioned in anterior cingulotomy for severe treatment-resistant depressive disorder (17), those areas stimulated in rapid-rate transcranial magnetic treatment for depression (18), and parallel aspects of the impact of cognitive behavioral therapy (19). The observed effects were entirely intracortical [including changes in functional connectivity between the neocortex and limbic cortex (e.g., DLPFC, anterior cingulate)], in contrast to connectivity studies exploring chemical antidepressant therapy, where subcortical limbic structures are implicated (12,13). Strikingly, the medial areas to which connectivity has been reduced (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…With regard to studies of treatment effects, reductions in functional connectivity observed here encompass the region lesioned in anterior cingulotomy for severe treatment-resistant depressive disorder (17), those areas stimulated in rapid-rate transcranial magnetic treatment for depression (18), and parallel aspects of the impact of cognitive behavioral therapy (19). The observed effects were entirely intracortical [including changes in functional connectivity between the neocortex and limbic cortex (e.g., DLPFC, anterior cingulate)], in contrast to connectivity studies exploring chemical antidepressant therapy, where subcortical limbic structures are implicated (12,13). Strikingly, the medial areas to which connectivity has been reduced (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Although such regional findings tend to correspond anatomically to those brain areas maximally activated by diverse emotional tasks in normal individuals (10), the nature (over-or underactivity) of the dysfunction seen in depressed subjects has seemed contradictory at times and its significance uncertain. Several recent functional imaging studies have focused on the investigation of functional connectivity among cortical and corticolimbic networks rather than the description of stimulus-induced or task-related activity in individual regions of interest (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The neural correlates of emotion processing and attention shifting evoked by our task were localized in areas that are usually not connected with response to antidepressant treatment in patients with MDD. [75][76][77] Owing to variability in the duration of treatment, it is also possible that some of the patients may not have responded to treatment yet.…”
Section: Figmentioning
confidence: 99%
“…Moreover, FCS reduction in the dorsomedial PFC was significantly associated with symptom improvement. However, since the treatment outcomes of the SSRI class of antidepressants cannot be extrapolated to norepinephrine reuptake inhibitors [88][89][90][91], another study focused on the treatment effect of duloxetine-a dual serotonin-norepinephrine reuptake inhibitor-in MDD using MRI [92]. This study showed a group-by-time interaction in the anterior DMN in which MDD patients presented increased functional connectivity with treatment, and that reduced baseline resting-state connectivity in the orbitofrontal component of the anterior DMN is a predictor of greater clinical response.…”
Section: Mr Imaging Of Resting-state Functional Connectivitymentioning
confidence: 99%